Enhancing RMG Supply Chain Efficiency through Automation: A Path to Cost Reduction in Bangladeshs Garment Industry (Global Journal of Management and Business Research, 2023)
Abstract not found
Keywords: transportation; RMG sector; supply chain analysis; logistics optimization; supply chain efficiency; industry 40 in logistics; logistics efficiency